PENYUSUNAN LAPORAN KEUANGAN BERDASARKAN STANDAR AKUNTANSI KEUANGAN ENTITAS MIKRO, KECIL DAN MENENGAH (SAK EMKM) (STUDI KASUS PADA “UMKM DEK DWIPA” PASAR BANYUASRI) - PUTU EKA NOPIYANI; MERTYANI SARI DEWI; NI MADE WULAN SARI SANJAYA; NI WAYAN ANI SAVITRI (GANEC SWARA, 2024)
This research was aimed to obtain descriptive findings about the financial statemens of UMKM Dek Dwipa 2022, the financial statements of UMKM Dek Dwipa 2022 in accordance with Financial Accounting Standards (FAS), and comparison between the financial statements of UMKM Dek Dwipa and UMKM Dek Dwipa financial statements which were prepared in accordance with Financial Accounting Standards (FAS) in 2022. The methods used in collecting the data were dokumentation, interviews, and literature. The results showed that the financial statements which were prepared by UMKM Dek Dwipa were not in accordance with Financial Accounting Standards (FAS). The financial statements which were prepared by UMKM Dek Dwipa only conssted of Income Statements, while financial statements in Financial Accounting Standards (FAS) there are Income Statement, Retained Earnings Reports, Balance Sheet, and Statement of Cash Flows. A difference was found between the financial statements prepared by UMKM Dek Dwipa and the financal statements prepared accordance whith Financial Accounting Standards (FAS). The difference lies in the amount of operational cost.